2020
DOI: 10.1038/s41586-020-2498-z
|View full text |Cite
|
Sign up to set email alerts
|

Glypicans shield the Wnt lipid moiety to enable signalling at a distance

Abstract: A relatively small number of proteins have been suggested to act as morphogens, signalling molecules that spread within tissues to organize cell fate specification during development and tissue repair. Among them are Wnt proteins, which carry a palmitoleate moiety that is essential for signalling activity 1-3 . How can a hydrophobic lipoprotein spread in the aqueous extracellular space? A variety of mechanisms, some invoking lipoprotein particles, exosomes or a specific chaperone, have been proposed to overcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 52 publications
(11 reference statements)
1
84
0
Order By: Relevance
“…Glypicans regulate several morphogenetic gradients in addition to that of Hh (ie.Wnt, Bmp, FGF). It has also been described that Dlp class of glypicans shields the highly hydrophobic lipid moiety of Wnts from the aqueous environment helping to be handed over to Wnt receptors (McGough et al ., 2020). Dlp could hide the lipids while transferring Hh to its receptor Ptc.…”
Section: Discussionmentioning
confidence: 99%
“…Glypicans regulate several morphogenetic gradients in addition to that of Hh (ie.Wnt, Bmp, FGF). It has also been described that Dlp class of glypicans shields the highly hydrophobic lipid moiety of Wnts from the aqueous environment helping to be handed over to Wnt receptors (McGough et al ., 2020). Dlp could hide the lipids while transferring Hh to its receptor Ptc.…”
Section: Discussionmentioning
confidence: 99%
“…However, Wntless does not migrate with the lipidated Wnt into the extracellular space [15]. The glypicans protect the lipid of Wnt proteins in the extracellular aqueous environment and act as a reservoir from which Wnt proteins can be passed to their receptors [16]. Structural studies have recently shown that these carrier proteins also utilize a palmitoleate binding pocket and provide further insight into this mechanism at a molecular level [16,17].…”
Section: Notum Deactivates Wnt Signalingmentioning
confidence: 99%
“…Specifically, N-sulfo-rich glypicans form clusters that colocalize with Wnt8/Fzd/Lrp6 puncta in vivo in Xenopus embryos, acting as recruiting platforms that accumulate Wnt ligands and promote the assembly of Wnt signalosomes (Mii et al, 2017). Notably, glypicans of the Dlp (Dally-like protein) family have been recently shown to bind the Wnt palmitoleate through a hydrophobic tunnel in their core protein, shielding the lipid moiety from the aqueous environment and serving as reservoirs that hand Wnt proteins to signaling receptors (McGough et al, 2020). Furthermore, the presence of certain coreceptors may promote the enrichment of specific Wnt ligands within signalosomes, in a context-specific fashion.…”
Section: Initiating Wnt S I G Naling : a Ss Emb Ly Of The S I G Nalmentioning
confidence: 99%